Addendum: Centrality dependence of high-pT D-meson suppression in Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Arslandok, Mesut; Busch, Oliver; Deisting, Alexander; Glässel, Peter; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Ohlson, Alice; Oyama, Ken; et al. (Journal of high energy physics, 2017)
This is an addendum to the article JHEP 11 (2015) 205 [1]. The figures 3 (right), 4 (right) and 5 are updated with published results on non-prompt J/ψ-meson production from the CMS collaboration [2]. Open image in new window
Im Titel ist "T" tiefgestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
The ALICE Collaboration: J. Adam, V. Anguelov, M. Arslandok, O. Busch, A. Deisting, P. Glässel, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, A. Ohlson, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, Y. Wang, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und weitere]
Gesehen am 19.10.2018